NILAI-NILAI PENDIDIKAN UNGGUL PERSPEKTIF QS. LUQMAN AYAT 12-19 - Celine, Devi Rofidah; Thobroni, Ahmad Yusam (Jurnal Al-Fatih, 2024)
Talking about the values of superior education, without strong policies and a valuable educational mission, there is a possibility that it will fail. One of the reliable educational values with superior values. Revealed in the Quran, Surah Luqman, verses 12-19. The main purpose of this study is to analyze how these principles can be applied in the context of modern education to foster character development among young people. Using a qualitative approach, this study uses literature review and text analysis to explore the implications of Luqman's teachings on contemporary education. The findings of the study reveal that integrating social responsibility and religious values into educational practices significantly increases students' awareness of their rights and obligations in society. In addition, this study highlights that teaching values such as prayer, good behavior, and social justice not only fosters individual character but also promotes a harmonious society. Ultimately, this study underlines the important role of parental guidance and educational frameworks in shaping morally responsible individuals in today's complex social landscape.